Let the dead speak…comments on Dibble et al.'s reply to "Evidence supporting an intentional burial at La Chapelle-aux-Saints". (May 2016) - Rendu, William; Beauval, Cédric; Crevecoeur, Isabelle; Bayle, Priscilla; Balzeau, Antoine; Bismuth, Thierry; Bourguignon, Laurence; Delfour, Géraldine; Faivre, Jean-Philippe; Lacrampe-Cuyaubère, François; Muth, Xavier; Pasty, Sylvain; et al.
Abstract: In a reply to our paper presenting new evidence supporting an intentional Neanderthal burial at La Chapelle-aux-Saints (Corrèze, France), Dibble et al. (2015) reviewed our data in relation to the original Bouyssonie publications. They conclude that alternative hypotheses can account for the preservation of the human remains within a pit. Here we present new data from our recent excavations and highlight several misinterpretations of the Bouyssonie publications, which, when taken together refute most of their arguments. Moreover, we show that the different hypotheses proposed by Dibble et al. cannot work together and fail to provide a credible explanation for the deposit, reinforcing our demonstration that the burial hypothesis remains the most parsimonious explanation for the preservation of the Neanderthal skeletal material at La Chapelle-aux-Saints. Highlights: We published in the PNAS new evidence sustaining the burial hypothesis at la Chapelle. Dibble et al. reviewed our data in the context of the Bouyssonie's publications. Their criticisms are based on mis-interpretation of the Bouyssonie publications. Their criteria fail to characterize numerous burials when applied to archaeological contexts. At the end, the burial hypothesis is by far the most parsimonious one for La Chapelle.